Parenting stress in parents with and without a mental illness and its relationship to psychopathology in children: a multimodal examination - Seipp, Vanessa; Hagelweide, Klara; Stark, Rudolf; Weigelt, Sarah; Christiansen, Hanna; Kieser, Meinhard; Otto, Kathleen; Reck, Corinna; Steinmayr, Ricarda; Wirthwein, Linda; Zietlow, Anna-Lena; Schwenck, Christina (Frontiers in psychiatry, 2024)
OBJECTIVE: Children of parents with a mental illness are at heightened risk to develop a mental illness themselves due to genetics and environmental factors. Although parenting stress (PS) is known to be associated with increased psychopathology in parents and children, there is no study investigating PS multimodally in a sample of parents with a mental illness. This study aims to compare PS of parents with and without a mental illness and further to examine the relationship between PS and psychopathology of children. - METHODS: Participants were parents with a mental illness and parents without a mental illness and their children aged four to sixteen years. We assessed PS multimodally using a questionnaire, parents' evaluation of children's behavior (relational schemas) and psychophysiological arousal of parents during free speech task. - RESULTS: Self-reported PS was increased, and evaluation of children's behavior was more negative and less positive in parents with a mental illness compared to parents without a mental illness. Children's psychopathology was associated with self-reported PS and relational schemas of parents. Regarding psychophysiological arousal, parents with a mental illness showed reduced reactivity in heart rate from baseline to free speech task in comparison to parents without a mental illness. - CONCLUSIONS: Our findings highlight the importance of implementing intervention programs to reduce PS for parents and children. In particular, parents with a mental illness might benefit from specific intervention programs in order to interrupt the transgenerational transmission of mental disorders.
Gesehen am 31.07.2024